Remodeling of glial coverage of glutamatergic synapses in the rat nucleus tractus solitarii after ozone inhalation. (1st July 2015) - Chounlamountry, Keodavanh; Boyer, Bénédicte; Penalba, Virginie; François‐Bellan, Anne‐Marie; Bosler, Olivier; Kessler, Jean‐Pierre; Strube, Caroline
Abstract Besides the well‐described inflammatory and dysfunction effects on the respiratory tract, accumulating evidence indicates that ozone (O3) exposure also affects central nervous system functions. However, the mechanisms through which O3 exerts toxic effects on the brain remain poorly understood. We previously showed that O3 exposure caused a neuronal activation in regions of the rat nucleus tractus solitarii (NTS) overlapping terminal fields of vagal lung afferents. Knowing that O3 exposure can impact astrocytic protein expression, we decided to investigate whether it may induce astroglial cellular alterations in the NTS. Using electron microscopy and immunoblot techniques, we showed that in O3‐exposed animals, the astrocytic coverage of NTS glutamatergic synapses was 19% increased while the astrocyte volume fraction and membrane density were not modified. Moreover, the expression of glial fibrillary acidic protein and S100β, which are known to be increased in reactive astroglia, did not change. These results indicate that O3 inhalation induces a glial plasticity that is restricted to the peri‐synaptic coverage without overall astroglial activation. Taken together, these findings, along with our previous observations, support the conclusion that O3‐induced pulmonary inflammation results in a specific activation of vagal lung afferents rather than non‐specific overall brain alterations mediated by blood‐borne agents. <boxed-text content-type="graphic" id="jnc13193-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text> Exposure to ozone, a major atmospheric pollutant, induces an increase in the glial coverage of neurons that is restricted to peri‐synaptic compartments. This observation does not support the view that the ozone‐induced neuronal disorders are related to non‐specific overall brain alterations. It rather argues for a specific activation of the vagus nerve in response to pulmonary inflammation.